Impact behaviour of aluminum particles upon aluminum, magnesium, and titanium substrates using high pressure and low-pressure cold spray - Abreeza Manap; Savisha Mahalingam; Siti Nurul Akmal Yusof; Nurfanizan Afandi; Huda Abdullah (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study is focused on the impact and residual stress behaviour of aluminum component repair using aluminum powder via two different types of cold spray processes; high pressure cold spray (HPCS) and low-pressure cold spray (LPCS). It has been carried out via smoothed particle hydrodynamics simulations, comparing aluminum substrate with other lightweight materials such as titanium and magnesium. The obtained results have shown that the impact behaviour is influenced by velocity, porosity, deformation behaviour, flattening ratio, total energy and maximum temperature. The aluminum particles impacting on aluminum substrates using LPCS is slightly deformed, with the smallest flattening ratio leading to less pore formation between the particles. This has subsequently resulted in good coating quality. Furthermore, HPCS has contributed greatly to the deposition of particles on the heavier and harder substrate, such as titanium substrate. Thus, the overall result indicates that LPCS is better for repairing aluminum component compared to HPCS.